2019
DOI: 10.2116/analsci.18p461
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of the Bursaphelenchus Xylophilus by Denaturation Bubble-mediated Strand Exchange Amplification

Abstract: that the pathogenic species B. xylophilus and non-pathogenic related species B. mucronatus have very similar morphologies, 9 the operation staff has required specialized knowledge about the nematode morphology, and it is extremely difficult to distinguish the pathogenic species from non-pathogenic related species. In recent years, polymerase chain reaction (PCR)-based detection methods for nematodes have been developed, such as conventional 10 or real-time PCR. 11 Real-time PCR can offer an accurate diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Primer design and establishing an optimal SSEA assay As previous studies have shown that the design of SEA primers was as simple as PCR, a variety of nucleic acid hybridization parameters were calculated to assess the primer quality. 24,25 To improve the amplification specificity and sensitivity, two sets of forward and reverse primers were designed and deployed simultaneously in the SSEA method (Table S1 †). The basic principle of SSEA reaction is based on the generation of denaturation bubbles and guanidine hydrochloride-mediated promotion of primers and template sequence binding.…”
Section: Resultsmentioning
confidence: 99%
“…Primer design and establishing an optimal SSEA assay As previous studies have shown that the design of SEA primers was as simple as PCR, a variety of nucleic acid hybridization parameters were calculated to assess the primer quality. 24,25 To improve the amplification specificity and sensitivity, two sets of forward and reverse primers were designed and deployed simultaneously in the SSEA method (Table S1 †). The basic principle of SSEA reaction is based on the generation of denaturation bubbles and guanidine hydrochloride-mediated promotion of primers and template sequence binding.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, isothermal DNA amplification techniques that do not require the use of thermal cycling apparatus have been applied to detect B. xylophilus. These include loop-mediated isothermal amplification (LAMP) (Kikuchi et al, 2009;Meng et al, 2018;Ahuja and Somvanshi, 2021), denaturation bubblemediated strand exchange amplification (SEA) (Liu C. et al, 2019), and recombinase polymerase amplification (RPA) (Cha et al, 2019(Cha et al, , 2020Fang et al, 2021). RPA, an isothermal nucleic acid amplification method that has attracted much attention because it is sensitive, rapid, works at isothermal temperature (Piepenburg et al, 2006;Glökler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, isothermal DNA amplification techniques that do not require the use of thermal cycling apparatus have been applied to detect B. xylophilus. These include loop-mediated isothermal amplification (LAMP) Ahuja and Somvanshi, 2021), denaturation bubble-mediated strand exchange amplification (SEA) (Liu C. et al, 2019), and recombinase polymerase amplification (RPA) (Cha et al, 2019(Cha et al, , 2020Fang et al, 2021). RPA, an isothermal nucleic acid amplification method that has attracted much attention because it is sensitive, rapid, works at isothermal temperature (Piepenburg et al, 2006;Glökler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%